What gets measured matters : is violence against women on the HIV and AIDS funding agenda? (Washington : Action Aid, 2008)
This report analyses the policies, programming and funding patterns of the four largest public donors to HIV&AIDS: the Global Fund to Fight AIDS, Tuberculosis and Malaria, the President's Emergency Fund for AIDS Relief (PEPFAR/US), the UK Department for International Development (DFID), and the World Bank, and UNAIDS (the Joint UN Programme on HIV/AIDS).
A one year review of show us the money: Is violence against women and girls on the HIV agenda?( from container)
DVD
Keywords: Violence -- United States; HIV Infections -- Economics -- United States; Acquired Immunodeficiency Syndrome -- Economics -- United States